IMPLEMENTATION OF SERVICE POLICY ASPECTS IN ACHIEVING EXCELLENT SERVICE IN PERBAUNGAN DISTRICT, SERDANG BEDAGAI REGENCY - Jonni Hutagalung; Audia Junita; Indra Muda; Rudi Salam Sinaga (Pena Cendekia Insani, 2026)
This study aims to analyze the implementation of service policy aspects, including Service Standards, Public Satisfaction Surveys (SKM), and Service Information, in an effort to realize excellent service at the Perbaungan Sub-district Office, Serdang Bedagai Regency. This study uses a qualitative approach with a descriptive research type. Data collection was conducted through in-depth interviews with purposively selected informants, including policy formulators (Organization and Legal Section of the District Secretariat), policy implementers (Sub-district Head, Section Head, staff, and counter officers of Perbaungan Sub-district), internal supervisors (Inspectorate), and community service users. The results of the study indicate a significant gap between policy formulation and implementation. Policy formulation is top-down and normative, with minimal participation from implementers and field research.